COVID-19-Fear Affects Current Safety Behavior Mediated by Neuroticism—Results of a Large Cross-Sectional Study in Germany - Fink, Madeleine; Bäuerle, Alexander; Schmidt, Kira; Rheindorf, Nadine; Musche, Venja; Dinse, Hannah; Moradian, Sheila; Weismüller, Benjamin; Schweda, Adam; Teufel, Martin; Skoda, Eva-Maria (Frontiers in Psychology, 2021)
Objectives. Although much research concerning personality and behavior changes in time of COVID-19 pandemic emerged, important questions still have not been answered. This study with a large sample aims to give insights into the impact of personality on pandemic fear and behavior by investigating the Big Five traits, COVID-19-fear, and associated behavioral changes in a large German-speaking sample. Methods. 14,048 healthy respondents (65.5% female, 34.2% male, 0.32% other gender/gender queer; range = 18 to 85 years, median age 35 to 44 years) participated in the survey during the COVID-19 pandemic. Two scales, ‘adherent’ (ASB, α = .857) and ‘dysfunctional’ safety behavior (DSB, α = .876), 3-items each, measured pandemic associated behavior. The BFI-10 tested personality traits. Results. While ASB correlated negatively with extraversion (rho = -.053, ≤ .001), the other four traits were positively associated, with the highest association for neuroticism (rho = .116, ≤ .001). Whereas neuroticism showed a positive correlation (rho = .142, ≤ .001) with DSB, extraversion (rho = -.042, ≤ .001), agreeableness (rho = -.028, ≤ .001), and conscientiousness (rho = -.025, ≤ .001) correlated negatively with it. Regression analyses showed a small extent of the effect of personality traits. Moreover, neuroticism mediated the association between COVID-19-fear and DSB (positive-directed). Conclusion. Even though, our results on correlations between personality, pandemic fear, and related behavior are in line with existing literature, the analyses clearly show that the impact of personality traits, including neuroticism, on pandemic behavior is very small. Rather, pandemic fear has a much larger influence on safety behavior mediated through neuroticism. Further studies should bear in mind that personality traits can not only have influencing but also mediating effects.